Cardiac sarcoidosis - Małgorzata Niemiec; Bartosz Gruchlik; Jan Niemiec; Magdalena Balwierz; Katarzyna Mizia-Stec (Śląski Uniwersytet Medyczny w Katowicach, 2023)
Cardiac sarcoidosis (CS) is a rare and difficult-to-diagnose condition that leads to conduction disorders, arrhythmias, and sudden cardiac death. Diagnosing CS is extremely difficult because it can be asymptomatic in its early stages and often mimics other conditions. The diagnostic tools used in the diagnosis of CS are: echocardiography, magnetic resonance imaging, positron emission tomography and biopsy of the affected tissue. Treatment involves the use of drugs that suppress the immune system. Some of the arrhythmias and conduction disturbances associated with CS may be reversible, but more often they require protection with devices such as pacemakers or defibrillators. More research is needed to develop more effective diagnostic strategies to improve the detection and treatment of this condition.